Embodiment in cognition and culture - Krois, John Michael (Advances in consciousness research, 2007)
This volume shows that the notions of embodied or situated cognition, which have transformed the scientific study of intelligence have the potential to reorient cultural studies as well. The essays adapt and amplify embodied cognition in such different fields as art history, literature, history of science, religious studies, philosophy, biology, and cognitive science. The topics include the biological genesis of teleology, the dependence of meaning in signs upon biological embodiment, the notion of image schema and the concept of force in cognitive semantics, pictorial self-portraiture as a me.